Penggunaan Natrium Tripolifosfat untuk Meningkatkan Masa Simpan Daging Ayam - Leny Yuanita; Prima Retno Wikandari; Sri Poedjiastoeti; Siti Tjahyani (agriTECH, 2009)
The aim of the study was to know the storage period of chicken on the usage of sodium tripolyphosphate ). The study was carried on two stages. The first stage, the Post Test Only Control Group Design, was to find the variation of sodium tripolyphosphate concentration and the length time of soaking to meet the requirement of P2O5 content and the quality of chicken muscle. The independent variables were sodium tripolyphosphate concentration and soaking time; while the dependent ones were: P O content and organoleptic parameter (i.e. color, flavor, texture). The second stage, the Fac- torial Design, was to know the storage period. The independent variables were variation of sodium tripolyphosphate concentration and soaking time, and storage period; while the dependent variables were chemical and microbiological quality. Data analysis were qualitative and quantitative descriptive. The results of the first stage study revealed that the variation of the sodium tripolyphosphate concentration and soaking time to meet the requirement of P2O5 content and the quality of chicken musle were: 55 g/l – 20 minutes, 70 g/l – 10 minutes, and 70 g/l – 20 minutes. The second stagestudy showed that the storage period of chicken muscle was 6 hours when variations of 70 g/l sodium tripolyphosphate concentration and 20 minutes soaking time were applied, variation of 70 g/l sodium tripolyphosphate concentration and 10 minutes soaking time was 3 hours storage period; while variation of 50 g/l sodium tripolyphosphate concentra- tion and 20 minutes soaking time, for less than 3 hours storage period.ABSTRAKPenelitian ini bertujuan mengetahui masa simpan pada penggunaan natrium tripolifosfat untuk daging ayam. Pene- litian terdiri dari 2 tahap. Tahap I mengetahui variasi konsentrasi natrium tripolifosfat dan lama perendaman yang memenuhi syarat kadar P2O5 dan kualitas daging ayam melalui rancangan penelitian the Post Test Only Control Group Design; variabel bebas adalah variasi konsentrasi natrium tripolifosfat dan lama perendaman, sedangkan variabel terikat adalah kadar P O dan mutu organoleptik. Tahap II mengetahui masa simpan  melalui rancangan penelitian faktorial; variabel bebas adalah variasi konsentrasi natrium tripolifosfat  dan lama perendaman, serta masa simpan, sedangkan variabel terikat adalah mutu kimia dan mikrobiologi. Analisis data secara deskriptif kuantitatif dan kuali- tatif. Hasil penelitian tahap I: Variasi konsentrasi natrium tripolifosfat dan lama perendaman yang memenuhi syarat kadar P2O5 dan kualitas daging ayam adalah 55 g/l- 20 menit, 70 g/l - 10 menit, dan 70 g/l - 20 menit. Hasil penelitian tahap II: Masa simpan daging ayam pada penggunaan natrium tripolifosfat 70g/l – lama perendaman 20 menit ada- lah 6 jam, untuk variasi 70g/l – lama perendaman 10 menit  adalah  3 jam; sedangkan variasi 50 g/l – lama perendaman 20 menit untuk masa simpan  < 3 jam.